2008
DOI: 10.1007/s00520-008-0412-6
|View full text |Cite
|
Sign up to set email alerts
|

Information to cancer patients: ready for new challenges?

Abstract: The article by Bracci et al. on information to cancer patients in three different geographic areas in Italy, published in this issue of our journal, provides empirical evidence that attitudes and practices of disclosure to cancer patients have evolved in Italy [3]. A shift toward truth telling began in Italy and in many other countries in the late 1980s-early 1990s [26,32]. Under the influence of many intertwined medical, legal, and societal changes, patients' information and involvement in decision making reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…This is similar to the findings of a recent Iranian study, which revealed a correlation between illiteracy and being unaware of the true diagnosis [25]. As new technologies become more accessible, patients increasingly seek, and obtain medical information outside clinical encounters, generally through mass media or the Internet [26]. This is especially true for those of younger age and higher education [27].…”
Section: Discussionsupporting
confidence: 83%
“…This is similar to the findings of a recent Iranian study, which revealed a correlation between illiteracy and being unaware of the true diagnosis [25]. As new technologies become more accessible, patients increasingly seek, and obtain medical information outside clinical encounters, generally through mass media or the Internet [26]. This is especially true for those of younger age and higher education [27].…”
Section: Discussionsupporting
confidence: 83%
“…This finding is in accordance with the study undertaken by Brokalaki et al [43], which reported that the patients who were high school and university graduates showed significantly superior levels of comprehension when compared to the patients who were graduates of elementary schools. Because technologies have become more accessible, patients with cancer increasingly seek and obtain information about their disease and treatment generally using the mass media or the Internet [45]. Considering that our patients were outpatients and one-third of them had a college or higher education level, it might have been easier for them to access the information of prognostic awareness.…”
Section: Discussionmentioning
confidence: 98%
“…This factor may be considered by some theorists as the core of moral distress, since it more explicitly refers to an ethical realm (7,38,39). Deceptive or misleading communication, such as giving "false hopes" or not discussing death with a dying patient, may not be a rare occurrence in clinical practice especially in the field of critical care and oncology where truth-telling may be perceived as difficult and painful for both clinicians and patients (40,41). Although in the From a practical perspective, the multidimensionality of the Italian MDS-R will allow a more accurate assessment of moral distress and the implementation of tailored interventions addressing the components of moral distress that will be found out to be more critical for a specific ICU or for a specific professional category.…”
Section: Discussionmentioning
confidence: 99%